2023
DOI: 10.15587/1729-4061.2023.273788
|View full text |Cite
|
Sign up to set email alerts
|

Damage formations of ramie fiber composites multilayer armour system under high-velocity impacts

Abstract: Multilayer armour system (MAS) becomes the best choice in reinforcing protection for military officers against projectile attack which has a high velocity of up to 7.62×51 mm NATO ball lead core (projectile level III NIJ standard) or AP 7.62×51 mm hard steel core (projectile level IV NIJ standard). This study aimed to analyze the damage formation of wolfram carbide (WC) ceramic and ramie fiber composites. The frontmost MAS uses WC ceramic and is enveloped by a back layer of ramie fiber composites with epoxy re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…CTBN is physically in the form of liquid rubber, which functions to fill in the gaps in the interfacial bonds between polyester, MASF and HTBF fibers. This phenomenon is supported by the results of a study [17], which concluded that CTBN elastic strain, the flexibility of the polyester, causes the tensile strain to increase. The increase in tensile strain has the effect of expanding the stretched area so that, if there is a shock load, more energy is absorbed.…”
Section: Discussion Of the Effect Hybrid Fiber And Filler Reinforcing...mentioning
confidence: 54%
“…CTBN is physically in the form of liquid rubber, which functions to fill in the gaps in the interfacial bonds between polyester, MASF and HTBF fibers. This phenomenon is supported by the results of a study [17], which concluded that CTBN elastic strain, the flexibility of the polyester, causes the tensile strain to increase. The increase in tensile strain has the effect of expanding the stretched area so that, if there is a shock load, more energy is absorbed.…”
Section: Discussion Of the Effect Hybrid Fiber And Filler Reinforcing...mentioning
confidence: 54%
“…Ramie is used for Multilayer Armor Systems (MAS) and shows the anti-ballistic properties of a composite of three layers of ceramic (wolfram carbide) and 10 layers of ramie nonwoven with epoxy resin as the matrix [ 61 ]. The suggestion to use crosslinked CA–ramie produced in this study made it possible to reduce the thickness of the fiber layer used.…”
Section: Discussionmentioning
confidence: 99%
“…The paper [23] It is shown that phenomena ceramic fragmentation occurs at an optimal thickness which capable of withstanding 7.62×51 mm Lead core and 7.62×51 mm hard steel core penetration. This becomes a problem when the panel has been fired multiple times.…”
Section: The Effect Of Sic Ceramic Coating Addition To Ramie Composit...mentioning
confidence: 97%